BL02U1: the relocated macromolecular crystallography beamline at the Shanghai Synchrotron Radiation Facility - Liu, Ke; Zhou, Huan; Xu, Qin; Kong, Hua-Ting; Zhang, Kun-Hao; Wang, Wei-Wei; Li, Min-Jun; Wang, Zhi-Jun; Pan, Qiang-Yan; Wang, Xing-Ya; Yu, Feng; Wang, Qi-Sheng (Nuclear science and techniques, 2023)
Macromolecular crystallography beamline BL17U1 at the Shanghai Synchrotron Radiation Facility has been relocated, upgraded, and given a new ID (BL02U1). It now delivers X-rays in the energy range of 6–16 keV, with a focused beam of 11.6 µm × 4.8 µm and photon flux greater than 10 12 phs/s. The high credibility and stability of the beam and good timing synchronization of the equipment significantly improve the experimental efficiency. Since June 2021, when it officially opened to users, over 4200 h of beamtime have been provided to over 200 research groups to collect data at the beamline. Its good performance and stable operation have led to the resolution of several structures based on data collected at the beamline.